Türkiye’de Sosyal Devlet Harcamalarının Genel Eğilimi: 2001–2009 Yılları Arasında Yapılan Eğitim, Sağlık Ve Sosyal Koruma Harcamaları - Senem Kurt Topuz (Alternatif Politika)
While listing the characteristics of the Republic by the constitution enactors in 1982 Constitution of Turkish Republic, it was stated that Turkish Republic is a “social state of law”. Within this context, it is expected that Turkish Republic, as required by being a social state, aim both to expand social welfare and try to realize social justice. The “social” characteristic of the state contains important quantitative means to examine this qualification of hers by looking at education, health, and social security expenditures. While education, health and social security (such as social insurance expenditure and housing, unemployment, disability, impairment, and illness aids) expenditures are considered crucial for the present and future of the society, these expenditure items are also taken as the basic requirements of being a social state according to the functional classification principle. In this study, first of all, the elements of the social state, the historical development of understanding of social state and structural resources of social state are empahized. Then, the constitutional foundations for understanding the social state in Turkey is explained. To examine the phenomenon of social state in Turkey, general tendency of the education, health, and social security expenditures of the state between the years 2001-2009 are analyzed. Moreover, status of Turkey is also mentioned among the member countries of OECD and European Union by comparing those with Turkey in regards to these three expenditure items. If the general tendency of aforementioned expenditure items between years 2001-2009 is examined, it is confirmed that there is no noteworthy increase during the period taken though it is seen that there is a significant increase on each item but those remain as little differences if their share within GDP is analyzed annually.